Modified fertilization management of summer maize (Zea mays L.) in northern China improves grain yield and efficiency of nitrogen use - Yi CHENG; Jie ZHAO; Zhen-xiang LIU; Zhi-jin HUO; Peng LIU; Shu-ting DONG; Ji-wang ZHANG; Bin ZHAO (Journal of Integrative Agriculture, 2015)
Improving the yield of maize grain per unit area is needed to meet the growing demand for it in China, where the availability of fertile land is very limited. Modified fertilization management and planting density are efficient methods for increasing crop yield. Field experiments were designed to investigate the influence of modified fertilization management and planting density on grain yield and nitrogen use efficiency of the popular maize variety Zhengdan 958, in four treatments including local farmer's practice (FP), high-yielding and high efficiency cultivation (HH), super high-yielding cultivation (SH), and the control (CK). Trials were conducted in three locations of the Huang-Huai-Hai Plain in northern China. Compared with FP, SH was clearly able to promote N absorption and dry matter accumulation in post-anthesis, and achieve high yield and N use efficiency by increasing planting density and postponing the supplementary application of fertilizers. However, with an increase in planting density, the demand of N increased along with grain yield. Due to the input of too much N fertilizer, the efficiency of N use in SH was low. Applying less total N, ameliorating cultivation and cropping management practices should be considered as priority strategies to augment production potential and finally achieve synchronization between high yield and high N efficiency in fertile soils. However, in situations where soil fertility is low, achieving high yield and high N use efficiency in maize will likely depend on increased planting density and appropriate application of supplementary fertilizers postpone to the grain-filling stage.